Patterns and Functions of Total Reduplication in Classical Arabic and Modern Standard Arabic:: A Corpus-Based Study - Modhaffer, Mohammed; Challavenkata, Sivaramakrishna (Linguistik Online, 2019)
In this paper, we investigate the form, salient patterns and core functions of word-level total reduplication in Classical Arabic (CA) and Modern Standard Arabic (MSA). Using a multi-genre corpus of 469 million words, we extract total reduplication (TR) candidates into an SQL database, manually filter them, and perform concordance search to identify the patterns and functions. Data analysis reveals nine patterns and eleven functions of TR and compares their relative frequency in each variety. The functions of TR are mapped into two broad categories: morphological and semantic/pragmatic. Results show an interesting variation in terms of top functions being favored by the two varieties. While TR is favored by CA to express serial ordering, MSA is noticed to favor it to express intensification. The empirical findings of this study provide a reliable quantification of the status of TR in CA and MSA which is rather difficult to obtain by theoretical means: on the one hand, TR in Arabic is not as productive as in other languages such as Indonesian. On the other hand, it is more common in CA than in MSA because the latter usually resorts to using loose phrases to express the same concepts expressed by TR in CA.